Synthesis of Chiral Primary Amines via Enantioselective Reductive Amination: From Academia to Industry - Shi, Yongjie; Rong, Nianxin; Zhang, Xumu; Yin, Qin (Synthesis, 2023)
Chiral primary amines widely exist in drugs and are exceptionally important subunits or synthons in the syntheses of chiral secondary and tertiary amines of medicinal interest. Metal-catalyzed enantioselective reductive amination (ERA) of ketones with ammonium salts or ammonia provides a direct method for their synthesis. Although very useful, progress in this field has been very slow and important advances have only been achieved in the last few years. Several major challenges exist in this reaction, including (1) the reversible formation of unstable NH-imine intermediates; (2) the strong coordination property of N-containing reagents toward metal species; and (3) the lack of efficient catalytic systems that enable high enantiocontrol. Generally, the efficiency and enantiocontrol of this reaction is dependent on the substrate type, for instance, the use of α-keto esters/amides or aryl alkyl ketones is well established and they have even been used in the industrial production of chiral amine drugs. However, highly enantioselective control in dialkyl ketones, cyclic ketones, and α-keto acids remains unsolved. Herein, the historical development of ERA reactions with ammonium salts or ammonia gas is summarized, and novel synthetic applications toward useful synthons or drugs are presented. In addition, the factors restricting the growth of this method are also discussed.1 Introduction2 Enantioselective Reductive Amination via Hydrogenation2.1 Enantioselective Reductive Amination of β-Keto Esters/Amides2.2 Enantioselective Reductive Amination of Simple Ketones2.3 Enantioselective Reductive Amination of α-Functionalized Ketones2.4 Enantioselective Reductive Amination/Cyclization Cascade Reactions2.5 Others3 Enantioselective Reductive Amination via Transfer Hydrogenation4 Synthetic Applications5 Conclusions and Outlook
Keywords: enantioselective reductive amination; chiral primary amines; drug synthesis; industrial applications; metal catalysis; ketones